2020
DOI: 10.1200/jco.2020.38.15_suppl.tps4122
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of durvalumab plus total neoadjuvant therapy (TNT) in locally advanced rectal cancer: The GEMCAD-1703 DUREC trial.

Abstract: TPS4122 Background: In clinical stages II and III (cT3-4 and/or N+), preoperative chemoradiotherapy (CRT) or short-course radiation followed by total mesorectal escision (TME) have been the standard of care for the last 15 years. Induction chemotherapy (CT) before CRT (strategy known as TNT) results in fewer toxic effects and improved compliance. TNT may release tumor-neoantigens with platinum-based induction CT, and radiotherapy has the potential ability to induce an immunogenic cell death and counteract an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In addition, immune checkpoint inhibitors such as durvalumab, avelumab, and nivolumab and other novel agents such as peposertib, a DNA protein kinase inhibitor, and aflibercept, an angiogenesis inhibitor, are being investigated in a TNT setting. 32 , 33 , 34 , 35 , 36 A list of recent and ongoing TNT trials that are yet to be published is included in eTable 2 in the Supplement . 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, immune checkpoint inhibitors such as durvalumab, avelumab, and nivolumab and other novel agents such as peposertib, a DNA protein kinase inhibitor, and aflibercept, an angiogenesis inhibitor, are being investigated in a TNT setting. 32 , 33 , 34 , 35 , 36 A list of recent and ongoing TNT trials that are yet to be published is included in eTable 2 in the Supplement . 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36] A list of recent and ongoing TNT trials that are yet to be published is included in eTable 2 in the Supplement. [30][31][32][33][34][35][36][37][38] Identifying predictive biomarkers for patients who are more likely to benefit from TNT is a current need. A National Cancer Database study 39 looked at more than 5000 patients and reported a significantly reduced rate of PCR after neoadjuvant CRT in patients with microsatellite instability (stability vs instability, 8.9% vs 5.9%; OR, 0.65).…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%
“…The AVACROSS study reported an increase in the pCR rate to 36% at the cost of more serious surgery-associated complications when bevacizumab was added to induction chemotherapy (32). Poly ADP-ribose polymerase inhibitors (e.g., veliparib) and DNA protein kinase inhibitors (e.g., peposertib) are being evaluated in combination with NACRT or chemotherapy before surgery during TNT (22,(33)(34)(35). However, these studies are at an exploratory stage, and relative sequence studies deserve consideration.…”
Section: Management Of Locally Advanced Crcmentioning
confidence: 99%
“…Optimal TNT strategies have not been established yet; type of chemotherapy agents vary between studies as well as the order in which chemotherapy and radiotherapy are being administered. Recently, there is a growing interest in the use of immunotherapy in the treatment of colorectal cancer and there are various ongoing TNT trials for patients with LARC who have added immunotherapy agents (durvalumab, nivolumab), DNA-dependent protein kinase inhibitors (peposertib), and poly ADP ribose polymerase inhibitors (Veliparib) to the TNT regimens [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: The Role Of Neoadjuvant Treatment Strategies In Exenteration...mentioning
confidence: 99%